Sistem Pendukung Keputusan Dalam Pemilihan Dokter Terbaik Menggunakan Metode Analytic Network Process (ANP) Berbasis Android (Studi Kasus Rsu Bhakti Medan) - Alimsyah, Alimsyah (JURIKOM (Jurnal Riset Komputer), 2019)
The selection of the best doctors at the Bhakti Medan public hospital has been done manually by assessing the number of patients who can be cured and from the opinions of the nurses who accompanied the doctor. However, this method cannot judge a doctor who works with professionals and has good quality. Therefore to be able to have a professional and quality doctor to improve the quality of health services. One effort to spur doctors' performance is by giving awards as the best doctor. One method that can be used to select a good doctor is the Analytic Network Process (ANP) method. The process that will be carried out in this study is to determine the criteria used to determine the best doctor based on performance evaluation in conducting health services and collecting data it is then calculated using the Analytic Network Process (ANP) method so that it can determine the best doctor optimally.